Beneficial Effects of Statins on the Rates of Hepatic Fibrosis, Hepatic Decompensation, and Mortality in Chronic Liver Disease: A Systematic Review and Meta‐Analysis. (October 2017) - Kamal, Sehrish; Khan, Muhammad Ali; Seth, Ankur; Cholankeril, George; Gupta, Deepansh; Singh, Utkarsh; Kamal, Faisal; Howden, Colin W; Stave, Christopher; Nair, Satheesh; Satapathy, Sanjaya K; Ahmed, Aijaz
Abstract : Objectives: Statins may improve outcomes in patients with chronic liver disease (CLD). We conducted a systematic review and meta‐analysis to evaluate the impact of statins in the setting of CLD. Methods: We searched several databases from inception to 17 October 2016 to identify comparative studies evaluating the role of statins in CLD. Outcomes of interest were the associations between statin use and progression of fibrosis, development of hepatic decompensation in cirrhosis, and mortality in CLD. Adjusted hazard ratios (HRs) were pooled and analyzed using a random effects model. Subgroup analyses were performed based on the method of detection for progression of hepatic fibrosis and quality of studies. Results: We included 10 studies (1 randomized controlled trial and 9 observational) with 259, 453 patients (54, 441 statin users and 205, 012 nonusers). For progression of hepatic fibrosis, pooled HR (95% confidence interval) was 0.49 (0.39–0.62). On subgroup analysis of studies using ICD‐9 (The International Classification of Diseases, Ninth Revision) coding and a second method to detect cirrhosis, pooled HR was 0.58 (0.51–0.65); pooled HR for studies using ICD‐9 coding only was 0.36 (0.29–0.44). For progression of fibrosis in patients with hepatitis C virus (HCV) infection, pooled HR was 0.52 (0.37–0.73). For hepatic decompensation in cirrhosis, pooled HR was 0.54 (0.46–0.65). For mortality, pooled HR based on observational studies was 0.67 (0.46–0.98); in the randomized controlled trial, HR was 0.39 (0.15–0.99). However, the quality of evidence for these associations is low as most included studies were retrospective in nature and limited by residual confounding. Conclusions: Statins may retard the progression of hepatic fibrosis, may prevent hepatic decompensation in cirrhosis, and may reduce all‐cause mortality in patients with CLD. As the quality (certainty) of evidence is low, further studies are needed before statins can be routinely recommended.